2020
DOI: 10.1097/dad.0000000000001847
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lichen Planus Associated With Lichen Planus Pigmentosus and Lichen Sclerosus in Monozygotic Twins

Abstract: Lichen planus (LP) is a mucocutaneous immunemediated disease of unknown etiology. It is more prevalent in women and usually occurs between the third and sixth decades of life. Oral lesions may or may not be associated with skin and genital lesions. Although the role of genetic factors is still undetermined, reports of LP in more than one family member are not uncommon. However, the occurrence of LP in monozygotic twins is rare. We report a rare case of 42-year-old female monozygotic twins presenting oral LP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Figure 2 shows that discoid lupus is highly associated with both lichen planus and lichen sclerosis and often overlap clinically [ 57 ]. Figure 3 shows they are also associated with sarcoidosis, erythema nodosum, and pyoderma gangrenosum, underlining a common genetic etiology [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows that discoid lupus is highly associated with both lichen planus and lichen sclerosis and often overlap clinically [ 57 ]. Figure 3 shows they are also associated with sarcoidosis, erythema nodosum, and pyoderma gangrenosum, underlining a common genetic etiology [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that LPP can occur with lichen planus (LP), as active or resolving LP lesions can be found in patients with LPP [ 5 , 13 ]. LPP also coexists with other variants of LP such as lichen planopilaris [ 14 ] and oral lichen planus (OLP) [ 15 17 ]. One study showed that LPP also correlates with autoimmune diseases such as Sjogren's syndrome, Crohn's disease, and rheumatoid arthritis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the influence of genetic factors remains uncertain, instances of Lichen Planus (LP) affecting multiple family members have been reported. Notably, a case involving two monozygotic twin sisters with oral LP has been documented, and one of them additionally exhibited LPP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%